2017
DOI: 10.5194/tc-2017-176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating interaction between surface water and groundwater in a permafrost region using heat tracing methods

Abstract: Abstract. Understanding the interactions between groundwater and surface water in permafrost regions is essential to the understanding of flood frequencies and river water quality of high latitude/altitude basins. The application of heat tracing methods, based on oscillating streambed temperature signals, is a promising geophysical method for identifying and quantifying the groundwater and surface water interactions. Analytical analysis based on one-dimensional convectiveconductive heat transport equation comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…By contrasting Control-NoSurf with Control-NoConv, we found many cooling events occurring at intermediate depths (0.4-1.3 m) within the soils and associated with upward water migration driven by the hydraulic gradient, resulting in higher simulated soil temperature simulated in NoConv (which completely removes the CHT process) than in Control. Some previous studies (Gao et al, 2020;Li et al, 2016) have reported that the melting occurring at the permafrost table provides water supply to the upper depths. Effects on the thermal and hydrological regimes of the entire active layer due to the upward liquid movement have also been reported Cui et al, 2020;Rowland et al, 2011).…”
Section: Bidirectional Thermal Impacts Of Convective Heat Transfermentioning
confidence: 97%
“…By contrasting Control-NoSurf with Control-NoConv, we found many cooling events occurring at intermediate depths (0.4-1.3 m) within the soils and associated with upward water migration driven by the hydraulic gradient, resulting in higher simulated soil temperature simulated in NoConv (which completely removes the CHT process) than in Control. Some previous studies (Gao et al, 2020;Li et al, 2016) have reported that the melting occurring at the permafrost table provides water supply to the upper depths. Effects on the thermal and hydrological regimes of the entire active layer due to the upward liquid movement have also been reported Cui et al, 2020;Rowland et al, 2011).…”
Section: Bidirectional Thermal Impacts Of Convective Heat Transfermentioning
confidence: 97%
“…Measuring the temperature is fast and less costly than measuring the solute concentration. Moreover, it is an environmental tracer—variations in groundwater temperature already occur naturally due to the surface water or fracture inflows [11]. Active heat tracing experiments involve either heating a discrete volume of groundwater or injecting hot/cold water into an aquifer [12,13].…”
Section: Introductionmentioning
confidence: 99%